2023
DOI: 10.1021/acs.molpharmaceut.2c00947
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Nanodrugs to Destroy the Tumor Extracellular Matrix Barrier for Improving Drug Delivery and Cancer Therapeutic Efficacy

Abstract: One of the main reasons why most cancer patients do not respond well to chemotherapy is that drugs cannot accumulate in tumors at an optimal dose, eventually resulting in failure to prevent cancer cell growth. To improve drug delivery efficiency, we engineered a highly efficient tumor-targeted and stroma-breaking nanocarrier by the modification of iron oxide nanoparticles (IONPs) with a tumor-targeting peptide c(RGDyK) and a hyaluronidase (HAase) on the surface. The yielding nanocomplex, c(RGDyK)-HAase-IONP, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In vitro, c(RGDyK)-HAase-IONP carrying DOX showed good biostability and a preferred drug release profile at low pH. After intravenous injection in MC38 tumor-bearing mice model, c(RGDyK)-HAase-IONP exhibited a 2.5 times higher tumor-targeting effect [ 107 ].…”
Section: Application Of Ha-modified Non-noble M-nps and Other Substit...mentioning
confidence: 99%
“…In vitro, c(RGDyK)-HAase-IONP carrying DOX showed good biostability and a preferred drug release profile at low pH. After intravenous injection in MC38 tumor-bearing mice model, c(RGDyK)-HAase-IONP exhibited a 2.5 times higher tumor-targeting effect [ 107 ].…”
Section: Application Of Ha-modified Non-noble M-nps and Other Substit...mentioning
confidence: 99%
“… 5 , 6 Recent studies have revealed that in vivo barriers and multidrug resistance (MDR) of cancer cells might contribute significantly to this drawback. 7 , 8 In vivo barriers encompass the complex physiological environment within living organisms that can impede the effective delivery and distribution of therapeutic agents to target cancer cells. 9 Factors such as the tumor microenvironment, 10 heterogeneous blood supply and drug metabolism, 11 and the presence of physiological barriers like the blood–brain barrier 12 contribute to the intricate landscape that influences drug accessibility and efficacy.…”
Section: Introductionmentioning
confidence: 99%